2021
DOI: 10.1080/14737167.2021.1939687
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of long-term real-world reduction in healthcare resource utilization following treatment of opioid use disorder with reSET-O, a novel prescription digital therapeutic

Abstract: Maricich (2021): Evidence of long-term real-world reduction in healthcare resource utilization following treatment of opioid use disorder with reSET-O, a novel prescription digital therapeutic, Expert Review of Pharmacoeconomics & Outcomes Research,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Also, consistent with previous analyses [ 26 ], reductions in healthcare utilization and costs over the 12-month period were greater in the reSET-O cohort vs. controls (− $2791). A subgroup analysis of Medicaid patients vs. controls showed an even greater difference in favor of reSET-O treated patients (− $3832/patient over 12 months), which carries important financial implications for states as they disproportionately bear the burden of the OUD epidemic and its ever-increasing costs.…”
Section: Discussionsupporting
confidence: 89%
“…Also, consistent with previous analyses [ 26 ], reductions in healthcare utilization and costs over the 12-month period were greater in the reSET-O cohort vs. controls (− $2791). A subgroup analysis of Medicaid patients vs. controls showed an even greater difference in favor of reSET-O treated patients (− $3832/patient over 12 months), which carries important financial implications for states as they disproportionately bear the burden of the OUD epidemic and its ever-increasing costs.…”
Section: Discussionsupporting
confidence: 89%
“…Several cases that utilized retrospective data for the evaluation of DTx have been found. In the case of Pear Therapeutics’ reSET and reSET-O, cost-effectiveness was analyzed in 351 opioid use disorder patients based on post-market insurance claims data [ 25 , 26 ]. Similarly, retrospective cohort data were used to analyze the therapeutic effects [ 27 ] or conduct an economic analysis [ 28 ] of DTx for patients with type 2 diabetes and hypertension.…”
Section: Evaluation Using Real-world Datamentioning
confidence: 99%
“…Velez et al report similar findings with a PDT focused only on opioid use disorder (OUD), reSET-O® but on a longer timescale and in comparison to controls. Previous analyses [ 18 20 ] have shown that patients treated with reSET-O had net cost reductions at 6 and 9 months post-treatment vs. control driven by reductions in the use of acute care services. The current study corroborates these results and is the first long-term (12-month) real-world analysis demonstrating a robust durability of response to treatment with PDT-delivered CBT among patients with OUD who are being concurrently treated with buprenorphine pharmacotherapy.…”
Section: Commentarymentioning
confidence: 99%